Localized State-Change Consensus in Immense and Highly Dynamic Environments - Linir Zamir; Mehrdad Nojoumian (Cryptography, 2022)
Consensus algorithms are the building block of any decentralized network where the risk of malicious users is high. These algorithms are required to be robust, scalable, and secure in order to operate properly. Localized state-change consensus (LSC) is a consensus algorithm that is specifically designed to handle state-change consensus, where the state value of given data points can dynamically change and the new value needs to be reflected in the system. LSC utilizes a trust measurement mechanism to validate messages and also enforce cooperation among users. Consensus algorithms, and specifically LSC, can be a practical solution for the immutable and secured communication of autonomous systems with limited computational resources. Indeed, distributed autonomous systems are growing rapidly and the integrity of their communication protocols for coordination and planning is still vulnerable because several units are required to act independently and securely. Therefore, this paper proposes a new localized consensus algorithm for immense and highly dynamic environments with validations through reputation values. The proposed solution can be considered as an efficient and practical consensus solution for any paradigms with resource-constrained devices where a regular encrypted communication method can negatively affect the system performance.